"It Feels like Diversity as Usual": Navigating Institutional Politics as LGBTQ+ Professionals. Issue 1 (1st January 2021) - Pryor, Jonathan T.; Hoffman, Garrett D.
Abstract : LGBTQ+ affairs professionals are often marginalized in their work and identities and therefore develop strategies to resist this continued marginalization. Using a critical conceptual framework, the traditionally heterogendered institution (THI), we show how LGBTQ+ affairs staff resist bureaucratic systems in their praxis to center LGBTQ+ (and other minoritized) identities on their campuses and how administrators who supervise LGBTQ+ affairs professionals might improve their praxes and better support LGBTQ+ affairs professionals.